Comparing Black-Scholes and GARCH Models in Long Strangle Option Strategies for LQ45 Index - Hendrawan, Riko; Safar, Abdul (Research of Finance and Banking, 2023)
This study compared the Black-Scholes and GARCH models in a long strangle strategy applied to the LQ45 index using closing price data from 1998 to 2021. It aimed to assess the benefits, calculate returns during crises and non-crisis periods, and evaluate performance through Average Mean Square Error (AMSE). The Black-Scholes model consistently outperformed GARCH in one- and three-month options. One-month options had an average return of 28.64%, and three-month options, 43.31%. In crises, Black-Scholes delivered average profits of 43.36% for one-month and 45.14% for three-month options. In non-crisis conditions, profits averaged 26% for one-month and 42.84% for three-month options. Model performance varied by option type and market context. Black-Scholes excelled in one-month call options (1.268% error), while GARCH performed better in one-month put options (1.0981% error). For three-month options, GARCH outperformed in call options (1.270% error), and Black-Scholes dominated put options (3.117% error). In summary, the choice between models should consider market conditions, favoring GARCH during crises and Black-Scholes in non-crisis scenarios.